Detection of the oxa-23 Gene, Marker of Carbapenem Resistance in Acinetobacter baumannii Isolates from RSUD Dr. Moewardi Surakarta - Dewangga, Vector Stephen; Nirwana, Ardy Prian; Setiyaningrum, Ratna (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Acinetobacter baumannii is a pathogenic germ that is a major problem in cases of hospital-acquired infections. The mortality rate for cases of infectious diseases caused by A. baumannii reaches 23% in hospitalized patients. The increase in the incidence of A. baumannii infections is in line with the increase in the incidence of resistance to antibiotics. The oxa-23 gene is known to be one of the causes of carbapenem resistance in A. baumannii. This study aims to detect the presence of the oxa-23 gene that causes carbapenem resistance in A. baumannii isolates originating from RSUD Dr. Moewardi Surakarta. The research was carried out in a descriptive observational, using Polymerase Chain Reaction (PCR) and electrophoresis techniques, using 20 clinical isolates of A. baumannii obtained from the RSUD Dr. Moewardi. From this research, results were obtained for 8 clinical isolates of A. baumannii from Dr. Moewardi was detected positively as having the oxa-23 gene, so it can be concluded that 40% of the total samples of A. baumannii isolates from RSUD Dr. Moewardi Surakarta was detected to have the oxa-23 gene which causes carbapenem resistance.